The Role Of Notary And Land Deed Official (PPAT) In The Process Of Waqf (Endowments) Deed Making - Muhammad Fatih Wahab Alhaddafi; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this study were 1) To determine the role of the Notary and the Land Deed Official (PPAT) in the manufacturing process Waqf deed, 2) to determine the obstacles and solutions Notary and Land Deed Official (PPAT) in the manufacturing process of Waqf deed.The method used in this research is normative juridical approach is the approach taken by the primary legal materials by means of studying the theories, concepts, principles of law as well as legislation related to this research. The specifications research used in this research is descriptive, which aims to unravel the facts to obtain an overview, on current issues, Based on the results of this study concluded that 1) The role of the Notary and the Land Deed Official (PPAT) In Preparation of Deed of Endowment. In the Act the existing regulations, a notary and land Deed Official (PPAT) does not have a role in making the Deed of Endowment. In fact, people need the help of Notary and land Deed Official (PPAT) in the process of making the Deed of Endowment for the maintenance of soil and conditions and Nadzir Wakif need can be helped by a Notary and land Deed Official (PPAT). 2) Constraints Notary and Land Deed Official (PPAT) In Preparation of Deed of Endowment. In this case the Notary and Land Deed Official (PPAT) has a problem because in Undan Act, Notary and Land Deed Official (PPAT) does not have the authority to make direct Waqf Deed. And so Notaries Land Deed Official (PPAT) can only help in the maintenance requirement is needed in the manufacture of Waqf Deed. 3) Solutions Notary and Land Deed Official (PPAT) In Preparation of Deed of Endowment. The best solution is awaiting a government decision stating that a Notary Public or Land Deed Official (PPAT) can be Endowment Deed Official Pledge (PPAIW). Thus simplifying wakif and nadzir to make Endowment Deed without going through a long process.Keywords: Roles; Notary; Land Deed Official (PPAT); Endowment Deed